1981
DOI: 10.1021/jm00141a019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of liver alanine aminotransferase activity by some benzophenanthridine alkaloids

Abstract: The quaternary benzophenanthridine alkaloids sanguinarine (1) and chelerythrine (2) inhibit rat liver L-alanine-:2-oxoglutarate aminotransferase (EC 2.6.1.2) activity. Nitidine (3) has no inhibitory effect. The inhibitory activity of alkaloids depends on the reactivity of the iminium bond with the nucleophilic reagent, e.g., the thiol group. The stability constants of adduct formation for thioethanol, cysteine, and glutathione with sanguinarine (1) and chelerythrine (2) are given. The mechanism of the inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 2 publications
3
38
1
Order By: Relevance
“…For example, rat liver alanine aminotransferase is inhibited by adduct formation between thiol groups of the enzyme and the iminium bond of chelerythrine (16). Chelerythrine also inhibits taxol-mediated polymerization of rat brain tubulin (32), histone kinase activity using partially purified PKC from the rat lacrimal gland (33), pyrogen-induced expression of tissue factor in endothelial cells, histamine release induced by aggregation of IgE-receptor on human basophils (34,35), Na ϩ ,K ϩ ,2Cl Ϫ cotransporter in Ehrlich mouse ascites tumor cells (36), and invasion of metastatic human follicular thyroid cancer (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rat liver alanine aminotransferase is inhibited by adduct formation between thiol groups of the enzyme and the iminium bond of chelerythrine (16). Chelerythrine also inhibits taxol-mediated polymerization of rat brain tubulin (32), histone kinase activity using partially purified PKC from the rat lacrimal gland (33), pyrogen-induced expression of tissue factor in endothelial cells, histamine release induced by aggregation of IgE-receptor on human basophils (34,35), Na ϩ ,K ϩ ,2Cl Ϫ cotransporter in Ehrlich mouse ascites tumor cells (36), and invasion of metastatic human follicular thyroid cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…Biological responses mediated by chelerythrine, such as cytotoxic activity with L-1210 tumor cells (14) and antiplatelet activity (15), have been ascribed to inhibition of PKC. Additional activities mediated by chelerythrine include inhibition of alanine aminotransferase (16), inhibition of Na ϩ ,K ϩ -ATPase (17), and antibacterial effects (18). In searching for novel natural product cancer chemopreventive agents, the benzophenanthridine alkaloid angoline was obtained from an extract of Macleaya cordata (Papaveraceae); this plant extract had previously been shown to antagonize the interaction of [ 3 H]phorbol 12,13-dibutyrate (PDBu) with PKC receptor.…”
mentioning
confidence: 99%
“…IQAs interconvert between the cationic vs. neutral form; they penetrate the cell membrane in the form of nonpolar pseudobase [184]. The iminium bond, C6 = N + in the cationic form is susceptible to nucleophilic attack and plays a key role in inhibition of SH-proteins [185]. The binding of IQAs with human serum albumin and L-cysteine is radically weaker at pH 5.0 than at pH 7.4.…”
Section: Molecular Targets Of Secondary Metabolitesmentioning
confidence: 99%
“…The measurements of the concentration dependency of the inhibitory effects of sanguinarine, chelerythrine and nitidine revealed that alanine aminotransferase activity was inhibited only by alkaloids with substituents in position 9 and 10 of ring D. Sanguinarine was a more powerful inhibitor than chelerythrine. Nitidine, a structural isomer of chelerythrine had no inhibitory effect even when a tenfold concentration compared to that of sanguinarine and chelerythrine was used (Walterova et al, 1981). Chelidonine, sanguinarine, and chelerythrine are natural benzophenanthridine alkaloids that inhibit taxol-mediated polymerization of rat brain tubulin in the micromolar range.…”
Section: Pharmacologymentioning
confidence: 99%